"(Not) forever talk": restaurant employees managing occupational stigma consciousness. Issue 4 (12th November 2018) - Shigihara, Amanda Michiko
Abstract : Purpose: The purpose of this paper is to examine restaurant employees' engagement in identity work to manage occupational stigma consciousness. Design/methodology/approach: Research methods included ethnographic fieldwork and in-depth interviews. Findings: Widespread societal stigma attached to food service work disturbed participants' sense of coherence. Therefore, they undertook harmonizing their present and envisioned selves with "forever talk, " a form of identity work whereby people discursively construct desired, favorable and positive identities and self-concepts by discussing what they view themselves engaged and not engaged in forever. Participants employed three forever talk strategies: conceptualizing work durations, framing legitimate careers and managing feelings about employment. Consequently, their talk simultaneously resisted and reproduced restaurant work stigmatization. Findings elucidated occupational stigma consciousness, ambivalence about jobs considered "bad, " "dirty" and "not real, " discursive tools for negotiating laudable identities, and costs of equivocal work appraisals. Originality/value: This study provides a valuable conceptual and theoretical contribution by developing a more comprehensive understanding of occupational stigma consciousness. Moreover, an identity work framework helps explain how and why people shape identities congruent with and supportive of self-concepts. Forever talk operates as a temporal "protect and preserve" reconciliation tool whereby people are able to construct positive self-concepts while holding marginalized, stereotyped and stigmatized jobs. This paper offers a unique empirical case of the ways in which people talk about possible future selves when their employment runs counter to professions normatively evaluated as esteemed and lifelong. Notably, research findings are germane for analyzing any identities (work and non-work related) that pose incoherence between extant and desired selves.